TNFRp55 controls regulatory T cell responses in Yersinia-induced reactive arthritis - Cargnelutti, Ethelina (2013)
In addition to its well-known pro-inflammatory effects, tumor necrosis factor (TNF) displays anti-inflammatory activities through mechanisms poorly understood. Previously, we reported the development of severe chronic Yersinia enterocolitica-induced reactive arthritis (ReA) in mice lacking the TNF receptor (TNFR)p55. As regulatory T (Treg) cells limit chronic inflammation, here we aim to investigate the expansion and function of CD4 þ CD25 þ FoxP3 þ Treg cells in the ReA animal model. The number of Treg cells as well as the FoxP3 mRNA expression and interleukin (IL)-10 levels were significantly decreased in joint regional lymph nodes (RLNs) of TNFRp55 / mice vs wild-type (WT) mice at the arthritis onset. However, at chronic phase of arthritis, the number of Treg cell in TNFRp55 / was similar to WT mice. To explore the in vivo function of Treg cells at this chronic phase in WT and TNFRp55-deficient mice, we adoptively transferred CD4 þ T cells from TNFRp55-deficient mice of day 21, into naı¨ve WT or TNFRp55 / mice. When knockout mice were used as recipients we observed higher delayed-type hypersensitivity (DTH) responses and joint inflammation after heat-killed Yersinia (HKY) stimulation. Accordingly, we found higher levels of IL-17, interferon (IFN)-c, IL-6, transforming growth factor-b1 and IL-12/23p40 and lower IL-10 levels in RLN of paws challenged with HKY in TNFRp55 / recipient mice. In addition, we found that CD4 þ T cells from TNFRp55 / mice controlled antigen-specific IL-12/23(p40) production in recipient WT mice. Our results show that TNFRp55 controls the induction and function of Treg cells through differential regulation of cytokine production, suggesting a novel molecular target for immune intervention in ReA.